KONFLIK DAN INTEGRASI DALAM MASYARAKAT PLURAL: JAMBI 1970-2012 - Lindayanti Lindayanti; Zaiyardam Zaiyardam (Paramita: Historical Studies Journal)
Jambi region was constituted by plural society. The social relations formed within a long period had created a conducive environment for plural society. The citizens were used to deal with people from different social and cultural background, and the differences of social class, religion, group and culture did not trigger conflict. Furthermore, interactions among ethnics, i. e. Melayu, Jambi, Minangkabau, Banjar, Bugis, Java and Batak even gave birth to new identity; the Jambi society. Nonetheless, the infiltration of big capital owners and trans-migration in 1990s had shaken this stability. The climax took place during the reformasi when a huge number of unrests surfaced, where society demanded the return of the land to the hands of people. It was important to build and employ attempts to lessen the tense and conflicts in this plural society. The local wisdom of Jambi people which has been formed for decades needed to be returned as a foundation for this attempt. Before capitalism dominated the life of the society, the values of local wisdom were proven to keep the plural society in harmony.